Pelaksanaan Pengangkatan Anak Menurut Hukum Adat Melayu di Kabupaten Rokan Hulu - Dini Anisa Putri; Hayatul Ismi; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Humans created by the god in the two types of men and women who has a sense of interest and need each other so intertwined a marriage to make a family. In a family that has been established then the child be something very expected for every couple. But not all of the couples are lucky in the blessed offspring. So the way to get the child by adopted a children (adoption). But adoption is not done for reasons blessed with offspring yet, but also cause the children’s parent can’t afford the children lives with the situation of children adopted by family / others. Adoption in every region in Indonesia has its own way and has the uniqueness. In society of Rokan Hulu adopted the children has way and . typical conditions. Customary adoption is mostly done by the society who are still strong with the customs. But after the adoption by using customary, they don’t request a court warrant as stipulated in the Indonesian government regulation No. 54 of 2007 about children adoption.This research is the sociological study of law, in this case the researchers immediately conduct investigation in complete and clear about the examined issues. The research is conduct by interview the traditional leaders and conduct questionnaires to married couples. In conducting this research, researchers want to know how the implementation of children adoption by Malay customary law in Rokan Hulu and what the legal consequences of the implementation of that children adoption.The results of this research is first in adoption of the children by Malay Customary Law of Rokan Hulu adoptive parents recourse to midwives who delivered the children lifted, with the agreement between the parents so the children is adopting with requiments of costum progenitor. Second, cause the law in adoption the children are considered part of the family adoption, adopted children entitled to an inheritance if the children has to appeal court decision in accordance with Article 9 paragraph 2 of the Indonesian Government Regulation No. 54 of 2007 about Adoption. Advice from the resecearhers is doing adoptions should be the court ruling so that the child has legal status and legal certainty so that the rights and obligations of children has a clear status. Keywords: Adoption, Malay Customary Law, Rokan hulu